PENGEMBANGAN PENUNTUN PRAKTIKUM MIKROBIOLOGI BERORIENTASI INKUIRI TERBIMBING UNTUK MAHASISWA STKIP PGRI SUMATERA BARAT - Sri Kenengsih (SAINTIFIK@, 2017)
Microbiology as constitute branch biology. Biology as a part of science process and product. Process that purpose is scientific skill that define problems, propose and test hypotheses, designing and assembling the instrument, process, pull conclusion, find to concepts. In order to this process and product existence is selected with the laboratory activities lab manual oriented guided inquiry. The purpose of this research was to product to microbiology lab manual oriented guided inquiry for students STKIP PGRI SUMBAR Padang that is valid, practical, and effective. This is a development research. This equipment was developed by using four-D models. That consists of define, design, develop, and disseminate stage. In the define stage, the analysis of curriculum, and of the students are collected. Meanwhile, the design stage has the planning of microbiology lab manual oriented guided inquiry. In the develop stage, validation and trial-error test toward students of STKIP PGRI SUMBAR Padang for the year of 2010 are conducted in order to know the practicality and effectivity of the lab manual oriented guided inquiry. Disseminate phase uncommitted coverage. Data collection instrument used in this study the validation sheet, practicality questionnaires for lecturers and students, student motivation questionnaire, observation of student activity sheets and tests students' learning outcomes. Then lab manual limited tested to 2101 E 36 and 2010 I 17 students in STKIP PGRI SUMBAR Padang. From the result of research can be determinated that lab manual oriented guided inquiry at valid category.Test result average validation of 79,35 (valid criteria), according to the lecturers practicality with scores 3,1 (practical criteria), according to the students practicality with scores 3,29 (practical criteria). The effectiveness of the motivation with scores 81,21 (effective criteria), according to the activities with scores 89,73 (effective criteria), and learning outcome pshycomotor with scores 89,51 (good criteria), affective with scores 89,34 (good criteria), and cognitive with scores 73,77 (pass criteria).Conclution of this research is developing microbiology lab manual oriented guided inquiry for students STKIP PGRI SUMBAR Padang stated was declared valid, practical and effective.Keyword: inkuiri terbimbing, penuntun praktikum, 4-D Model